PERANCANGAN PROGRAM APLIKASI PENDAFTARAN SISWA BARU DI SMA KESATRIAN 1 SEMARANG BERBASIS WEB (Information Technology and Telematics, 2015)
Abstract : Role in today's web is crucial to the transformation of information from one party to another party, such as in education. Registration of new students at the high school Kesatrian 1 Semarang still using manual systems, so it can be more difficult to irregular data collection, damage or loss of data from prospective new students, and errors in the calculation of the average value. This research was conducted with the results of the program design can overcome the existing problems in the registration system manually, therefore, the process of registration of new students at the high school Kesatrian 1 Semarang done online goal is to be able to facilitate the prospective new students to enroll without visiting the school and information registration can be accessed online. Systems development method in this application using prototyping method using the programming language PHP and MySQL database. Keywords Applications, PSB, Web Based